Assessment of physical weathering in bedrock areas at the Trinity Peninsula, Antarctica: Towards a classification of the current weathering grade in polar areas. (October 2022) - Ruiz-Pereira, S.; Beriain, E.; Cabré, A.; Cid-Agüero, P.
Abstract: The Antarctic Peninsula is one of the world's most rapidly warming regions; over the last hundred years, glaciers have retreated, exposing new rocky areas to physical weathering. In its northernmost part, the Trinity Peninsula, physical weathering processes on exposed bedrock between west and east coasts may not be at the same weathering stage as surface temperature conditions are assumed historically different. Thus, we examined rock outcrops in ice-free coasts, assessed surface temperature conditions, rock fracturing degree from rock samples, and analyzed the local context for permafrost occurrence. The survey through Trinity Peninsula covered a transect over three ice-free locations between Cape Legoupil and Düse Bay (63°30′S). Our findings support that ice-free-bedrock surfaces at both coasts of the Trinity Peninsula are at an early weathering stage under equivalent air temperature and wind speed conditions over the last decades. Temperature analysis indicated that if surface temperatures sustain its 2015–2016 magnitude, the permafrost distribution will likely become sporadic. Findings indicate that the physical weathering rates should have been significantly slower or have remained ice-covered much longer than in other areas of the Antarctic Peninsula. Nevertheless, a sustained surface warming will elicit higher physical weathering rates beyond the initial stage attested. Highlights: New insights on rock weathering stages in a remote Antarctic location. Combination of rock surface thermal, fracture, and connectivity analyses. Focus on intercoastal permafrost distribution over the last decades. Baseline to characterize and compare ice-free areas under current warming.